DAMPAK PERTUMBUHAN INDUSTRI TERHADAP KUALITAS AIR BERSIH DI PERKOTAAN - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2007)
AbstractÂ Accumulation of existence environmental pollution by industrial disposal, sea water instrusion, usage of water by inefficient resident and inexistence rejuvenation clean water in urban region causes water to have no again is considered to be renewable resource.Keyword: environmental pollution, clean water.